Penegakan Hukum Terhadap Tindak Pidana Penodaan, Penyalahgunaan, Dan Penistaan Agama Hindu Di Bali - I Putu Eka Saputra; Karolus Kopong Medan; Bhisa Vitus Wilhelmus (CV. Ulil Albab Corp, 2026)
This research is motivated by the increasing number of cases related to the use of Hindu symbols and teachings, which have provoked public reaction and the potential for social conflict in Bali. This issue is important because it relates to legal certainty in the application of Article 156a of the Criminal Code and the protection of religious values. This study aims to analyze the elements of the crimes of blasphemy, misuse, and defamation and examine the factors influencing law enforcement against these crimes in Bali. The research method used is empirical juridical with a normative and sociological approach, through literature review and interviews, followed by qualitative analysis. The results indicate that the objective elements in Article 156a of the Criminal Code are generally met, particularly regarding the elements of